2018
DOI: 10.18632/aging.101524
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration in aged mice: new insights

Abstract: The regenerative capacity of the liver after resection is reduced with aging. Recent studies on rodents revealed that both intracellular and extracellular factors are involved in the impairment of liver mass recovery during aging. Among the intracellular factors, age-dependent decrease of BubR1 (budding uninhibited by benzimidazole-related 1), YAP (Yes-associated protein) and SIRT1 (Sirtuin-1) have been associated to dampening of tissue reconstitution and inhibition of cell cycle genes following partial hepate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 234 publications
(297 reference statements)
2
31
0
1
Order By: Relevance
“…Sirtuin 1 (Sirt1) is a histone-deacetylase involved in the transcriptional control of metabolism, and its low activity has been associated with senescent phenotypes in several organs. (15,16) Supporting aging-mediated changes in Sirt1, we found that it was down-regulated in older mice on FFD and that Shc down-regulation in the LV or AAV8-injected model reversed this (Supporting Fig. S7A).…”
Section: Hepatocyte-specific Shc-deleted Mice Show Improvement In Nasmentioning
confidence: 70%
“…Sirtuin 1 (Sirt1) is a histone-deacetylase involved in the transcriptional control of metabolism, and its low activity has been associated with senescent phenotypes in several organs. (15,16) Supporting aging-mediated changes in Sirt1, we found that it was down-regulated in older mice on FFD and that Shc down-regulation in the LV or AAV8-injected model reversed this (Supporting Fig. S7A).…”
Section: Hepatocyte-specific Shc-deleted Mice Show Improvement In Nasmentioning
confidence: 70%
“…Conversely, prolonged exposure of keratinocytes to SASP provoked maintenance of the cells to a senescent status, implying overall that SASP acts as a double‐edged sword for tissue regeneration in a time‐dependent manner . In addition, chronic activation of HSCs due to aging or NASH and their subsequent chemokine and ROS production leads to decreased activation and proliferation of liver progenitor cells, which are required for liver regeneration following hepatic injury . Overall, further studies are essential to reveal the role of senescence in liver regeneration during NASH resolution.…”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 99%
“…(76) In addition, chronic activation of HSCs due to aging or NASH and their subsequent chemokine and ROS production leads to decreased activation and proliferation of liver progenitor cells, which are required for liver regeneration following hepatic injury. (77) Overall, further studies are essential to reveal the role of senescence in liver regeneration during NASH resolution.…”
Section: Nash Resolution and The Role Of Senescencementioning
confidence: 99%
“…On the one hand, there are significant changes in expression of crucial proteins like Yap or Sirt1, and lncRNAs in the aged mice and humans. [196][197][198] On the other hand, there is a clinical evidence that orthotopic liver transplants from aged donors are comparable to those from young donors. 199 We propose significant progress on the roles of ncRNA in aging liver as many transplants in clinic are from people more than 70 to 80 years old.…”
Section: Resultsmentioning
confidence: 99%